Sensor Characteristic Studies and Thermal Diffusivity Measurement of Tin (IV) Oxide-Based Ceramic Gas Sensors - Afindi Zaman, Rosyaini (2004)
The atmospheric pollution has lead to the research and development of a variety of sensors using different materials and technologies particularly for low cost and lower operating temperatures. An n-type semiconducting oxide such as tin oxide (SnO2) is one of the most important and extensively used materials for the detection of gases. In this project, the I-V characteristic and thermal diffusivity of pure SnO2 and SnO2- CuO was studied. The I-V characteristic was measured using two-probe technique while the thermal diffusivity was measured using a photoflash method. The X-Ray Diffraction was used for identification of the phase in the sample and Scanning Electron Microscopy (SEM) was used to provide supportive evidence for the factor causing the changes of the parameters included. These methods are important to confirm the existence of SnO2 peaks which is critical to CO2 gas. It was found that the I-V characteristics of sensor materials remain linear in a temperature range of 27 0C 340 0C both in air and CO2 environment. Sensor sensitivity was found to be dependent on temperature. Pure SnO2 showed maximum sensitivity (~2.5) at operating temperature 300 0C. Operating temperature is defined as the temperature that gas sensor give a maximum reaction (sensitivity) with tested gas. With addition of CuO into SnO2, the gas sensing temperature and electrical conductivity of the sensor was found to decrease. The operating temperature also rapidly decreased from 300 0C (pure SnO2) to 220 0C (addition of 40 mol% CuO). It is also observed that the annealing process has lowered the operating temperature of the sensor from 220 0C (sample as prepared) to 180 0C (samples annealed 600 0C, 700 0C and 800 0C). The effect of gas pressure on operating temperature did not change with increasing gas pressure but it showed higher sensitivity at higher gas pressure. The sensor response time was also studied as a function of SnO2 composition and gas pressure. It was found that by increasing the gas pressure, the sensor response time decreased. The addition of CuO also has lowered the response time of SnO2 from 10 minutes to 6 minutes. We found that 60 mol% SnO2 - 40 mol% CuO system which annealed at 600 0C, 700 0C and 800 0C has the best sensing properties and lower operating temperature at 180 0C. In this study, thermal diffusivity of SnO2 - CuO system and 60 mol% SnO2 - 40 mol% CuO system was in range of 1.4 to 7.8 x10-2 cm2/s.